Quantitative cell-cycle protein expression in oral cancer assessed by computer-assisted system - Soares, C. P. [UNESP]; Zuanon, J. A S [UNESP]; Teresa, D. B. [UNESP]; Fregonezi, P. A. [UNESP]; Benatti Neto, Carlos[UNESP]; Oliveira, M. R B [UNESP]; Donadi, E. A.; Martinelli-Kläy, C. P.; Soares, E. G. (My University, 2006)
The knowledge of cell-cycle control has shown that the capacity of malignant growth is acquired by the stepwise accumulation of defects in specific genes regulating cell growth. Histologic diagnosis might be improved by a quantitative evaluation of more specific diagnosis biomarkers, which could help to precisely identify pre-malignant and malignant oral lesions. The aim of the present study is to evaluate whether computer-based quantitative assessment of p53, PCNA and Ki-67 immunohistochemical expression, could be used clinically to foresee the risk of oral malignant transformation. This retrospective study was carried out in ninety-five oral biopsies, 27 were classified as fibrous inflammatory hyperplasia, 40 as leukoplakia and 28 as oral squamous cell carcinoma. Sixteen out of the 40 leukoplakia were diagnosed as non-dysplastic leukoplakia, the other 24 being dysplastic leukoplakia, of which 50.0% were classified as moderate to severe dysplasia. Comparison of the four groups of oral tissues showed significant rises in p53 and Ki-67 positivity index, which increased steadily in the order benign, pre-malignant, and malignant. In contrast, it was not possible to relate higher PCNA levels with pre-malignant and malignant oral lesions. We therefore conclude that PCNA immunohistochemistry expression is probably an inappropriate marker to identify oral carcinogenesis, whereas joint quantitative evaluation of p53 and Ki-67, appears to be useful as a tumor marker, providing a pre-diagnostic estimate of the potential for cell-cycle deregulation of the oral proliferate status.
Keywords: Computer-assisted analysis; Ki-67; Oral cancer; p53; PCNA; cell cycle protein; cycline; Ki 67 antigen; protein p53; tumor marker; carcinogenesis; cell cycle regulation; computer assisted diagnosis; computer system; controlled study; diagnostic accuracy; disease severity; epithelium hyperplasia; histopathology; human; human tissue; immunohistochemistry; leukoplakia; major clinical study; malignant transformation; mouth cancer; protein expression; quantitative analysis; retrospective study; risk assessment; squamous cell carcinoma; statistical significance; enzyme immunoassay; metabolism; mouth tumor; pathology; Carcinoma, Squamous Cell; Cell Cycle Proteins; Diagnosis, Computer-Assisted; Humans; Immunoenzyme Techniques; Ki-67 Antigen; Leukoplakia, Oral; Mouth Neoplasms; Proliferating Cell Nuclear Antigen; Retrospective Studies; Tumor Markers, Biological; Tumor Suppressor Protein p53